Results of Archaeometrical Studies on a Kontush Sash from Piaseczno (Pomorskie Province, Poland) - Miazga, Beata; Grupa, Dawid; Grupa, Małgorzata (the Authors, 2023)
Archaeometric studies on silk thread wound around with metal strips are still rarely undertaken in Poland. Their popularization seems to be necessary, however, as there are many problems to solve. In the case of a kontush sash manufactured in Gdańsk as archaeological finds, the main question is whether they used metal strips prepared by local craftsmen, what raw material was employed, and what methods of gilding were implemented. Only future regular studies and analyses can answer these questions. The article presents the results of tests on metal strips wound around silk threads coming from a kontush sash manufactured by Besch, excavated in the crypt under the presbytery of the church of the Nativity of the Blessed Virgin Mary in Piaseczno (Pomorskie voivodeship, Poland).
Keywords: silk thread with metal; kontush sash; crypt; Piaseczno; Poland; X-rays; SEM